UNVEILING THE RELATIONSHIP BETWEEN CUSTOMER RELATIONSHIP MANAGEMENT, INNOVATION CAPABILITY, AND SMALL AND MEDIUM SCALE ENTERPRISES’ PERFORMANCE - Tuamyil Betzoom, Rufina; Gontur, Silas; Davireng , Makrop (Journal of Allied Research in Management and Entrepreneurship (JARME), 2022)
Small and medium-sized enterprises (SMEs) are crucial to national and global economies. They contribute significantly to economic growth, job creation, and social inclusion. Despite their importance, SMEs still face various challenges, such as insufficient funding, poor planning, and inadequate resource management. This study aims to determine whether customer relationship management (CRM) influences SMEs’ performance in Nigeria’s Plateau state. The research adopts a mixed-method approach to examine the impact of CRM on customer retention, involvement, information sharing, organization, and technology-based methods, as well as innovation capability. Financial, customer, internal operations, and staff learning and development perspectives are also analyzed. The study uses in-depth interviews and structural equation modeling to evaluate the performance of SMEs in the area. The findings show that a business’s ability to innovate is strongly linked to its relationship with customers. The study recommends that SMEs adopt innovative strategies to enhance their relationships with customers and improve their performance.